PERSEPSI SISWA TERHADAP PEMBELAJARAN ONLINE MATAPELAJARAN BIOLOGI DI MASA PANDEMI COVID-19 - Yosi Amelia; Rahmawati Darussyamsu (Bioilmi: Jurnal Pendidikan, 2020)
Biology is a subject that plays an important role in determining the quality of education. However, the learning process including biology is currently not being carried out as usual (face to face) due to the covid-19 pandemic. This research was conducted to determine students' perceptions of online biology learning. The research method was carried out quantitatively by distributing questionnaires containing statement items with three dimensions of research focus, namely dimensions of teaching material, learning atmosphere / environment and student interaction during learning. Quantitative data analysis was performed using a Likert scale survey method with 100 respondents, namely students of class XI MIA SMAN 2 Sungai Penuh as a research sample. The results showed that the three dimensions of learning related to student perceptions, namely the dimensions of biology teaching material, learning atmosphere / environment and student interactions during online biology learning, got positive results. Researcher's positive findings do not mean there are no obstacles in the implementation of online biology learning. These obstacles include expensive internet quotas and difficult internet access.